2014
DOI: 10.1063/1.4862653
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure x-ray diffraction study of YBO3/Eu3+, GdBO3, and EuBO3: Pressure-induced amorphization in GdBO3

Abstract: Angle-dispersive synchrotron X-ray diffraction measurements were performed on vaterite-type YBO3/Eu3+, GdBO3, and EuBO3, respectively, up to 41 GPa at room temperature using a diamond-anvil cell. Pressure-induced amorphization was observed in hexagonal GdBO3 with a significant compression along the c-axis. Compared to the ions of the distorted GdBO3 phase, its anions may lose their long-range order prior to the cations at high pressures. Based on the experimental pressure-volume data, the obtained bulk moduli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 26 publications
5
31
0
Order By: Relevance
“…[11] to be 326 GPa, which the authors allege supports the earlier reported value of 321 GPa by Wang et al in Ref. [12]. In our previous work, Ref.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…[11] to be 326 GPa, which the authors allege supports the earlier reported value of 321 GPa by Wang et al in Ref. [12]. In our previous work, Ref.…”
Section: Introductionsupporting
confidence: 91%
“…(The data of Wang et al Ref. [12] are included in Fig. 3(a) for comparison, a detailed discussion of which is available in Ref.…”
Section: Critical Comparison Of Bulk Moduli With Reported Valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, such studies are relatively rare for borates, due probably to high mechanical stability of these compounds. For instance, YBO 3 :Eu 3 þ and EuBO 3 are stable up to 41 GPa [16]. However, Li 2 B 4 O 7 and GdBO 3 amorphize under high pressure conditions [16,17] whereas FeBO 3 and LiB 3 O 5 show presence of pressure-induced phase transitions at 22.7 and 5 GPa, respectively [18,19].…”
Section: Introductionmentioning
confidence: 97%